Effect of Taekwondo Training on Lower Body Strength and Balance in Young Adults with Down Syndrome. Issue 2 (June 2016) - Carter, Kathy; Horvat, Michael
Abstract: Research with individuals with Down syndrome (DS) suggests that increasing strength and balance may lead to increases in independence and self‐reliance. Taekwondo has been shown to increase strength and balance in typically developing (TD) individuals. A study was undertaken to determine whether Taekwondo training can improve lower body strength and balance of young adults with DS. Forty‐four adults with DS aged 21–30 years were assigned to either taekwondo classes 2 days/weeks for 10 weeks ( n  = 22) or a control group ( n  = 22). Measurements were taken prior to training, after 5 weeks and after 10 weeks of training, and after a 5 week detraining period. Strength was measured utilizing a hand‐held dynamometer. Balance tests utilized the modified Clinical Test for Sensory Integration and Balance (mCTSIB) with eyes open and closed, whereas dynamic balance was measured utilizing a limits of stability (LOS) test. A repeated measures MANOVA (significance level set at p  < .05) was utilized to determine differences between groups over time for each of the three assessments. It was found that there was a significant mean increase in lower body strength after 5 weeks (pre: 142.1 lbs ± 52.4; 5 week: 197.7 lbs ± 71.2), and an additional increase after 10 weeks of training (10 week: 227.9 lbs ± 74.9). A decrease in strength was shown after detraining (188.5 lbs ± 63.7). Strength measures for the control group remained unchanged. There were no significant differences seen between groups in static or dynamic balance. The authors concluded that Taekwondo can be an effective method to increase strength of individuals with DS. Additional research is needed to determine if these strength changes lead to benefits related to physical function and independence.